PROSEDUR LAYANAN KARANTINA HEWAN OLEH STASIUN KARANTINA PERTANIAN KELAS 1 AMBON PADA WILAYAH KERJA BANDARA PATTIMURA AMBON - Sarfan, Riri; Matatula, Michel; Sangadji, Insun; Tulalessy, Abraham; Sulaiman, Kitriyani (MAANU: Jurnal Pengabdian Kepada Masyarakat, 2024)
Animal Quarantine Services are regulated in Law Number 21 of 2019 concerning Quarantine of Animals, Fish, and Plants. This law aims to prevent the entry of new pests, diseases, and nuisance organisms into Indonesia's territory, as well as prevent their spread from one area to another. Animal quarantine service procedures at the Ambon Class 1 Agricultural Quarantine Station in the Pattimura Ambon airport work area implement 8 quarantine measures namely: Examination, Isolation, Observation, Treatment, Detention, Rejection, Destruction, and Release. The eight quarantine measures are intended for all animals, Materials of Animal Origin (BAH) and Products of Animal Origin (HBAH), and other objects brought from outside and within the work area of Pattimura Airport. and some of the documents that must be completed during the inspection of incoming and outgoing domestic goods. The conclusion drawn from this activity is that the animal quarantine service procedure at the Class 1 Agricultural Quarantine Station Ambon Pattimura Airport work area has been carried out in accordance with the 8th quarantine measures and No problems were found on any carrier media.